Positivityand stability of descriptor linear systems with interval state matrices - Качорек, Тадеуш; Kaczorek, Tadeusz (Lviv Politechnic Publishing House, 2018)
Досліджено позитивність та асимптотичну стійкість дескрипторних лінійних часово неперервних та дискретних систем з інтервальними матрицями стану та інтервальними поліномами. Встановлено необхідні та достатні умови для позитивності лінійних часово неперервних та дискретних систем. Показано, що опукла лінійна комбінація поліномів позитивних лінійних систем також є поліномом Гурвіца. Поширено теорему Харітонова на позитивні дескрипторні лінійні системи з інтервальними матрицями стану. Також встановлено необхідні та достатні умови для асимптотичної стійкості дескрипторних позитивних лінійних систем. Розглянуті припущення проілюс- тровано за допомогою числових прикладів.

The positivity and asymptotic stability of descriptor linear continuous-time and discrete-time systems with interval state matrices and interval polynomials are investigated. Necessary and sufficient conditions for the positivity of descriptor continuoustime and discrete-time linear systems are established. It is shown that the convex linear combination of polynomials of positive linear systems is also the Hurwitz polynomial. The Kharitonov theorem is extended to the positive descriptor linear systems with interval state matrices. Necessary and sufficient conditions for the asy mptotic stability of descriptor positive linear systems have been also established. The considerations have been illustrated by numerical examples.
Позитивність та стійкість дескрипторних лінійних систем з інтервальними матрицями стану
Keywords: interval; positive; descriptor; linear; system; stability; extension; Kharitonov theorem